2006
DOI: 10.1016/j.ijgo.2006.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Laser labioplasty of labia minora

Abstract: Patients expressed a high degree of satisfaction with laser labioplasty, which can be combined with other surgical gynecologic interventions without increased complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
1
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 13 publications
1
68
1
11
Order By: Relevance
“…A 5-point scale is used to rate each item ranging from [1] strong negative feelings to [5] strong positive feelings. The overall scale correlates well with self-esteem.…”
Section: Measures Of Total Body Esteemmentioning
confidence: 99%
See 2 more Smart Citations
“…A 5-point scale is used to rate each item ranging from [1] strong negative feelings to [5] strong positive feelings. The overall scale correlates well with self-esteem.…”
Section: Measures Of Total Body Esteemmentioning
confidence: 99%
“…2 Other studies have similarly been limited to functional and physical results of FGPS. [3][4][5][6][7][8][9][10] Bramwell et al 16 utilized semi-structured interviews to gain insight about psychological well-being of participants; their results revealed important individual variations in motivation, access, and response to surgery that were not detected in earlier research. In particular, most women initially reported feeling their genitals were "abnormal" and expressed the goal of achieving a "normal" (to them) genital appearance as the main reason for surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 21, 18 were reports of surgical procedures. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The remaining three papers were as follows: one qualitative study of patient experience after labial reduction, 20 one study of patient indications for surgery, 21 and one survey of women's attitudes to their labia. 22 Of the remaining 19 of the 40 publications that did not include surgical results, one was a description of a technique, 23 five were letters on points relating to the surgical technique, [24][25][26][27][28] and three were discussions of the surgical technique.…”
Section: Evaluation Of Research Methodologymentioning
confidence: 99%
“…(15,17) Labioplasty was generally performed on its own; in some studies it was performed in conjunction with other types of surgery including hysterectomy, perineoplasty, clitoral hood reduction or vaginal tightening. (6,15,61) Of the 18 studies on labioplasty, the majority reported the reasons for seeking surgery which were either medical/functional and/or aesthetic and/or psychosocial. Table 5.2 presents the proportion of patients reporting each type of reason for labioplasty, for those studies where the information was available.…”
Section: Clinical Indications For Vulvoplasty and Labioplastymentioning
confidence: 99%